The management of observatories in the internationalization of Higher Education in Latin America (GEON Journal (Management, Organizations and Business), 2019)
In this research we analyze the role of academic observatories for the internationalization of higher education, seeking to strengthen the linkage, interaction and integration of the various Latin American universities, both public and private, in order to manage the negotiation of education in the internationalization.The decision-making of educational institutions is supported by the analysis of updated information, clear and precise, these decisions promote the adaptation of new models of education crediting them in an international context, with the intention of qualifying the improvement of quality in the education and potentiate the development of the international, national and local economy to promote and promote the academic development of education, UNESCO works to create favorable conditions for collaboration between different societies, avoiding the disparity between the different countries
Keywords: Management; internationalizations; Education; Observatories